Perancangan Logo Kampanye Sosial “FLOW” Sebagai Media Edukasi PTSD pada Generasi Z - Rahma Elmira Fairuza; Aileena Solicitor Costa Rica El Chidtian; Pungky Febi Arifianto (Pixel :Jurnal Ilmiah Komputer Grafis, 2025)
This study aimed to design the visual identity of the social campaign FLOW (Find Lights Over Wounds) to promote early awareness of Post Traumatic Stress Disorder among Generation Z. A mixed method approach was applied to explore perceptions, knowledge, and the need for empathetic and communicative educational media. Data were collected through online questionnaires from 108 respondents and in-depth interviews with psychologists, psychiatrists, and PTSD survivors. The findings indicated that Generation Z required visual media that conveyed mental health messages safely and meaningfully. The FLOW logo was developed through brainstorming, sketching, and expert validation, featuring a heart and hands symbolizing empathy and healing. Soft blue, pink, and pastel yellow colors were used to create a calm, warm, and hopeful impression. The campaign effectively fostered emotional awareness and encouraged help-seeking behavior among young audiences.